Development of student worksheets integrated with islamic values to explore mathematical problem-solving skills in pesantren - Sofiani, Julia; Aripin; Rahayu, Diar Veni (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2024)
This development research aims to produce student worksheets integrated with Islamic values to enhance mathematical problem-solving skills on the Pythagorean Theorem topic. This type of research is Research and Development (R&D) using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of the small-scale trial involved 2 teachers and 10 ninth-grade students, while the field trial involved 25 eighth-grade students. The instruments used in this study were validation questionnaires to assess the feasibility of the worksheets by material experts, media experts, and Islamic experts. Additionally, to evaluate the effectiveness of the worksheets, student response questionnaires and the results of mathematical problem-solving skills tests were used. The results of the effectiveness analysis of the worksheets, calculated using the effect size, showed a value of 2.1 with a